Political science a global perspective - Morlino, Leonardo 1947-; Berg-Schlosser, Dirk; Badie, Bertrand (SAGE Publications Ltd, 2017)
From the award-winning team behind the International Encyclopaedia of Political Science ... Moving beyond mainstream "traditional" approaches to bring you a new advanced-level introduction to political science. A perfect introduction for postgraduates who are new to political science, as well as upper-level undergraduates looking to broaden and deepen their understanding of core topics, this progressive account: • Guides you through all key areas of political science: origins, methodological foundations, key topics, and current issues • Takes an international and pluralist perspective with all issues explored in a comparative way related to different cultural and historical contexts • Includes pulled-out descriptions of major concepts, further reading and self-assessment questions at the end of each chapter
Includes bibliographical references and index
Keywords: Political science; Political participation; Politische Wissenschaft; Lehrbuch